Haplotype-Phased Chromosome-Level Genome Assembly of Cryptoporus qinlingensis, a Typical Traditional Chinese Medicine Fungus - Yu Song; Ming Zhang; Yu-Ying Liu; Minglei Li; Xiuchao Xie; Jianzhao Qi (Journal of Fungi)
This study presents the first comprehensive genomic analysis of Cryptoporus qinlingensis, a classical folk medicine and newly identified macrofungus from the Qinling Mountains. Utilizing advanced sequencing technologies, including PacBio HiFi and Hi-C, we achieved a high-quality chromosome-level genome assembly. The genome, sized at 39.1 Mb, exhibits a heterozygosity of 0.21% and contains 21.2% repetitive sequences. Phylogenetic analysis revealed a recent divergence of C. qinlingensis from Dichomitus squalens approximately 212.26 million years ago (MYA), highlighting the rapid diversification within the Polyporaceae family. Comparative genomic studies indicate significant gene family contraction in C. qinlingensis, suggesting evolutionary adaptations. The identification of a tetrapolar mating system, along with the analysis of CAZymes and P450 genes, underscores the genomic complexity and ecological adaptability of this species. Furthermore, the discovery of 30 biosynthetic gene clusters (BGCs) related to secondary metabolites, including polyketide synthase (PKS), non-ribosomal peptide synthetase (NRPS), and terpene synthesis enzymes, opens new avenues for exploring bioactive compounds with potential medicinal applications. This research not only enriches our understanding of the Cryptoporus genus but also provides a valuable foundation for future studies aiming to harness the therapeutic potential of C. qinlingensis and to further explore its ecological and evolutionary significance.